2019
DOI: 10.1038/s41598-019-43054-4
|View full text |Cite
|
Sign up to set email alerts
|

UM171 expands distinct types of myeloid and NK progenitors from human pluripotent stem cells

Abstract: Scaling up blood cell production from hPSCs is critical to advancing hPSC technologies for blood transfusion, immunotherapy, and transplantation. Here we explored the potential of the HSC agonist pyrimido-indole derivative UM171, to expand hematopoietic progenitors (HPs) derived from hPSCs in chemically defined conditions. We revealed that culture of hPSC-HPs in HSC expansion conditions (SFEM with added TPO, SCF, FLT3L, IL3 and IL6) in the presence of UM171 predominantly expanded HPs with a unique CD34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Similarly, withdrawal of FGF2 reduced blood production in ETV2-induced cultures (Figure 2G). To test whether myeloid cell production can be improved with the use of other cytokines or small molecules, we tested the effects of FLT3L, SCF, and small-molecule UM171, which has been shown to stimulate expansion of human cord blood CD34 + cells ex vivo (Fares et al., 2014) and hPSC-derived myeloid progenitors enriched in G-CFCs (Mesquitta et al., 2019). We have found that the presence of SCF and FLT3L slightly decreased the number of collected floating cells during differentiation, while UM171 had no significant effect on the number of hematopoietic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, withdrawal of FGF2 reduced blood production in ETV2-induced cultures (Figure 2G). To test whether myeloid cell production can be improved with the use of other cytokines or small molecules, we tested the effects of FLT3L, SCF, and small-molecule UM171, which has been shown to stimulate expansion of human cord blood CD34 + cells ex vivo (Fares et al., 2014) and hPSC-derived myeloid progenitors enriched in G-CFCs (Mesquitta et al., 2019). We have found that the presence of SCF and FLT3L slightly decreased the number of collected floating cells during differentiation, while UM171 had no significant effect on the number of hematopoietic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Further, UM171 can act as a new substance to expand HSCs without the risk of chronic graft-versus-host disease (GVHD) and relapse [ 32 , 33 ]. Moreover, UM171 plays an important role in treating lymphoma [ 60 , 61 ]. A study explored the culture of hPSC-HPs in HSC expansion conditions.…”
Section: Ex Vivo Expansion Of Hscsmentioning
confidence: 99%
“…ESC-NK exerted good functional characteristics including cytokine production and cytolytic activity in vitro and in vivo against tumor cells ( Woll et al, 2005 ; 2009 ). Other groups have replaced the second stromal line with genetically engineered feeder cells expressing Notch ligand DLL1 or DLL4, which promote the expansion of HPCs with a bias for NK lineage ( Mesquitta et al, 2019 ; Zeng et al, 2017 ).…”
Section: Nk Cell Differentiationmentioning
confidence: 99%
“…In general, small molecules reduce the cost of product development while maintaining or even increasing the NK cell differentiation efficiency. For example, the Slukvin team showed that UM171, an HSC-agonist pyrimido-indole derivative, selectively promotes the expansion of a lymphoid progenitor population that has a 10-fold propensity for NK cell differentiation ( Mesquitta et al, 2019 ).…”
Section: Nk Cell Differentiationmentioning
confidence: 99%